Pre-service English language teachers’ perceptions towards teaching grammar (Journal of NELTA, 2018)
This article explores the perceptions of pre-service English language teachers studying at Master’s level under Education faculty at Tribhuvan University Nepal towards grammar and grammar teaching employing a qualitative research design. Three pre service English teachers were involved in this study, out of which two were females and one was male. The research participants were interviewed using a semi-structured interview technique to collect relevant information to fulfill its purpose. The finding several that pre-service English teachers are in favour of teaching grammar. However, they believe that grammar should not be taught giving rules directly. All of the participants favour the use of inductive method of teaching grammar though they were taught through the use of deductive method at school.